2021
DOI: 10.1080/21655979.2021.1951927
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an epithelial-mesenchymal transition related long non-coding RNA (LncRNA) signature in Glioma

Abstract: Epithelial-mesenchymal transition (EMT)-related long non-coding RNAs (lncRNAs) may be exploited as potential therapeutic targets in gliomas. However, the prognostic value of EMT-related lncRNAs in gliomas is unclear. We obtained lncRNAs from The Cancer Genome Atlas and constructed EMT-related lncRNA co-expression networks to identify EMT-related lncRNAs. The Chinese Glioma Genome Atlas (CGGA) was used for validation. Gene set enrichment and principal component analyses were used for functional annotation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…LncRNAs widely partake in the regulation of gene expression, thus playing an essential regulatory role in the malignant biological behaviors of tumor cells [ 26 ]. In glioma progression, lncRNA is also an important regulator.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs widely partake in the regulation of gene expression, thus playing an essential regulatory role in the malignant biological behaviors of tumor cells [ 26 ]. In glioma progression, lncRNA is also an important regulator.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological function of lncRNAs in the EMT process of GBM remains poorly understood. Recently, Tao et al screened EMT-associated lncRNAs in TCGA database and found nine EMT-associated lncRNAs and GBM patients with higher EMT-associated lncRNA expression had poorer overall survival ( Tao et al, 2021 ). However, the biological function and underlying molecular basis of EMT-associated lncRNAs still need to be characterized.…”
Section: Significance Of Lncrnas In Gbm Malignant Phenotypesmentioning
confidence: 99%
“…In addition, previous studies have attempted to reveal the prognostic impact of EMT on glioma. For example, Tao et al constructed an EMT-related lncRNAs prognostic model based on glioma samples and explored the predictive capability of EMT-related lncRNAs for the immune features ( Tao et al, 2021 ). However, this study has not fully explored the correlation of their prognostic model with genetic features, epigenetic modifications of DNA and RNA, stemness features, metabolism, the efficiency of radiotherapy and TMZ chemotherapy, and sensitivity to immune checkpoint blockade (ICB) therapy in LGG.…”
Section: Introductionmentioning
confidence: 99%